REGISTER SEPAK BOLA DALAM BUKU SEPAK “DOLAR” BOLA KARYA AMIR MACHMUD NS - Danik Ismawati; Henricus Supriyanto (Buana Bastra, 2020)
The purpose of this study is to describe 1) the forms of football registers used in the book “dolar” football by Amir Machmud NS; and 2) the meanings of football registers words and phrases used in the book “dolar” football by Amir Machmud NS. This study used a qualitative descriptive method with data collection techniques rafer to notice and record. The data analyses techniques in this study are 1) categorization; 2) presents the table; abalyses data; and taking conclusions. All findings data are chosen based on needing as much as 113 data conclusions of words and phrases from Indonesian, words and phrases fron English, and word and phrases that are a mixture of Indonesian and English. There are two findings in this research, 1) thirteen forms of football registers in the form of words and one hundred phrases totaling, with categories of verb words, nouns, numeral and categories of verb phrases, nouns phrases, adjective phrases; 2) the meaning of words and phrases of the football register is divided into two, namely the actual meaningful denotative or meaningful number of 45 and connotative or forty five meaningless words.